2021
DOI: 10.15507/1991-9468.103.025.202102.257-272
|View full text |Cite
|
Sign up to set email alerts
|

The Social Competences of High School Students from a Contextual Approach

Abstract: Introduction. The formation of social competences of schoolchildren is an important area of modern science and pedagogical practice. Despite the large number of publications on this issue, there is virtually no research on the analysis of social context, which largely determines the practical implementation of social competences. The aim of this article is to analyse the high schoolʼs activities on social competence development using a contextual approach. The novelty of the approach lies in the identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Research about social competencies of high school pupils (Tsvetkova & Ivanova, 2021) showed that, among social competencies, which were developed in high schools, the ones that stood out were ability to work with information, understand people, determine the propensity for science, independence, as well as a tolerant attitude towards people from other cultures. Over the past decade the number or students who believed that school prepared them for life significantly decreased.…”
Section: Students' Entrepreneurial Competenciesmentioning
confidence: 99%
“…Research about social competencies of high school pupils (Tsvetkova & Ivanova, 2021) showed that, among social competencies, which were developed in high schools, the ones that stood out were ability to work with information, understand people, determine the propensity for science, independence, as well as a tolerant attitude towards people from other cultures. Over the past decade the number or students who believed that school prepared them for life significantly decreased.…”
Section: Students' Entrepreneurial Competenciesmentioning
confidence: 99%
“…In some works of scientists and teachers (Poshtareva, 2007;Slastenin, Kashirin, 2010;Morozov, 2011aMorozov, , 2011b; Atheeque, 2017) and others present the problems of ethnopedagogy as the basis of ethno-cultural education. In modern pedagogical science (Tsvetkova, Ivanova, 2021;Soshnikov, 2014;Popova, 2019) ethno-cultural competence is considered as an important component of social competences. Scientists talk about methods that allow analyzing the social competences of students, considering the peculiarities of the social context.…”
Section: Introductionmentioning
confidence: 99%